Pengajian Tafsir di Kelantan: Satu Tinjauan Sejarah - Abdullah, Mustaffa; Yakob, Mohd Asmadi (Jurnal Usuluddin, 2003)
The article attempts to expose various types of studying the Qur'anic exegesis in the state of Kelantan. The teaching of Qur'anic exegesis has its foundation in the traditional Islamic educational institution of known as "pondok" and informal institutions such as mosque, surau and others. However, the teaching method of Qur'anic exegesis has changed due to the introduction of Islamic religious schools and Arabic schools in Kelantan. These formal Islamic educational institutions paid special attention to the teaching of Qur'anic exegesis in order to make students understand the contents of the holy Qur'an correctly and get the true teachings of Islam.